SARS-CoV-2 Mutations and their Viral Variants - Cosar, Begum; Karagulleoglu, Zeynep Yagmur; Unal, Sinan; Ince, Ahmet Turan; Uncuoglu, Dilruba Beyza; Tuncer, Gizem; Kilinc, Bugrahan Regaip; Ozkan, Yunus Emre; Ozkoc, Hikmet Ceyda; Demir, Ibrahim Naki; Eker, Ali; Karagoz, Feyzanur; et al. (ELSEVIER SCI LTD, 2022)
Mutations in the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) occur spontaneously during replication. Thousands of mutations have accumulated and continue to since the emergence of the virus. As novel mutations continue appearing at the scene, naturally, new variants are increasingly observed.Since the first occurrence of the SARS-CoV-2 infection, a wide variety of drug compounds affecting the binding sites of the virus have begun to be studied. As the drug and vaccine trials are continuing, it is of utmost importance to take into consideration the SARS-CoV-2 mutations and their respective frequencies since these data could lead the way to multi-drug combinations. The lack of effective therapeutic and preventive strategies against human coronaviruses (hCoVs) necessitates research that is of interest to the clinical applications.The reason why the mutations in glycoprotein S lead to vaccine escape is related to the location of the mutation and the affinity of the protein. At the same time, it can be said that variations should occur in areas such as the receptor-binding domain (RBD), and vaccines and antiviral drugs should be formulated by targeting more than one viral protein.
Keywords: COVID-19; Mutation; Receptor-binding domain; SARS-CoV-2; Spike protein; Viral variants; CORONAVIRUS; SPIKE; MECHANISMS; IDENTIFICATION; TRANSMISSION; REPLICATION; ACE2; COV; Biochemistry & Molecular Biology; Cell Biology